Towards Green and Smart Seaports: Renewable Energy and Automation Technologies for Bulk Cargo Loading Operations - Philipp Robert; Prause Gunnar; Olaniyi Eunice O.; Lemke Florian (Sciendo, 2022)
In 2018, 4.1 billion tonnes of freight and 437 million passengers passed through the 1200 European ports. This dimension of geographically concentrated activities is the rationale that ports are characterised by a high-energy demand and a high share of emissions. Driven by a growing awareness for a cleaner environment, a stronger focus on sustainability and intensified environmental regulations, ports are forced to take responsibility when it comes to environmental issues. As a response, in recent studies, the concept of ‘green ports’ emerged. Simultaneously, in the context of digitalisation, the term ‘smart ports’ has received growing attention in the latest scientific discussions, too. Since an important driver towards greener maritime operations is linked to digitalisation, we argue that digital efforts in ports should next to the automation of inherent logistics processes also contribute to reducing the emissions and energy demands. Previous studies have primarily concentrated on the automation of container handling operations. Hence, there exists a research gap concerning the automation of bulk cargo handling operations in ports. Thus, this study addresses the question of how to automate the dry bulk cargo loading operations in the frame of a green and smart port development. The developed case study refers to the seaport of Wismar, whereby the results show that the digitalisation and greener port operations can be successfully aligned. Overall, this study extends the discussion on green and smart port development, while it contributes to the scientific literature by proving that both conceptual ideas can be achieved in the operating business.